A Retrospective Study of 1, 098 Blood Samples with Anemia from Adult Cats: Frequency, Classification, and Association with Serum Creatinine Concentration. (September 2014) - Furman, E.; Leidinger, E.; Hooijberg, E.H.; Bauer, N.; Beddies, G.; Moritz, A.
<x xml:space="preserve">Abstract</x> Background Frequency and classification of anemia in terms of regeneration status and erythrocyte indices are not well described in cats. Objective To determine frequency and regenerative status of anemia in samples from adult cats, to assess the sensitivity and specificity of macrocytosis and hypochromasia for detecting regenerative anemia (RA), and to evaluate the association of anemia with increased serum creatinine concentration (SC). Study Population Laboratory records from 30, 503 blood samples from cats (2003–2011). Methods Clinicopathologic data reviewed retrospectively. Anemia defined as hematocrit (Ht) ≤27%, red blood cell count (RBC) ≤5.5 × 106/μL and hemoglobin (Hb) ≤9.0 g/dL. RA defined by manual absolute reticulocyte count >50 × 103/μL. Macrocytosis was defined as mean corpuscular volume (MCV) >55 fL and hypochromasia as mean corpuscular hemoglobin concentration (MCHC) <31 g/dL. Cutoff for increased serum creatinine concentration was 1.6 mg/dL. Results Overall, 1, 098 of 30, 503 blood samples (3.6%) from cats fulfilled criteria for anemia, 633 of 1, 098 (57.7%) classified as nonregenerative (NRA) and 465 of 1, 098 (42.3%) as regenerative. RBC, Ht, and Hb were significantly lower in the RA compared to NRA group (P < .05). Sensitivity and specificity of the combined high MCV and low MCHC to detect samples with RA were 19.5 and 90.7%. SC was increased in 572 of the 1, 098 anemic samples (52.1%) and in 11, 121 of 29, 405 of nonanemic samples (37.8%). Conclusions and Clinical Importance Majority of anemic samples were classified as NRA. Anemia was more severe in cats with RA. Erythrocyte indices were not sensitive indicators of RA.